Back Fat Thickness, Body Condition Score and Rib Eye Muscle Area of Young Sheep Fed with Carica Dieng Seeds Based on Ultrasonography - Tunggadewi, Faustina Helene; Idayanti, Rahma Wulan; Purnomoadi, Agung; Arifin, Mukh; Purbowati, Endang (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
A study to compare the back fat thickness, rib eye muscle area, and body condition score (BCS) of young thin-tailed lambs fed various levels of carica Dieng seeds in rations. Eighteen male lambs aged 3-4 months with an initial body weight of 10.68 ± 1.30 kg were applied three feeding treatments (T) following a completely randomized design, T1 = complete feed containing 5% carica seeds, T2 = complete feed containing 12.5% carica seeds, and T3 = complete feed containing 20% carica seeds, with six replications each. At the end of 14 weeks of feeding treatment, back fat thickness and rib eye muscle area were measured using the Digital Veterinary Ultrasound Imaging System CTS-800. Yield grade value was determined using back fat thickness data, while the BCS assessment was carried out visually. The results showed that various levels of carica seeds addition to complete feed did not produce significant differences (P>0.05) in all variables measured. Back fat thickness, BCS, and rib eye muscle area in young thin-tailed sheep were 1.46 mm, 3.06, and 15.52 cm2, respectively. It might be concluded that supplementation of carica Dieng seeds up to 20% in the complete feed can still be utilized by young thin-tailed sheep.